Analisis Yuridis Penerapan Business Judgement Rules dalam Tindak Pidana Korupsi Yang Dilakukan Oleh Direksi BUMN PT. Asabri Persero (Studi Putusan Nomor 13/Pid.Sus-Tpk/2022/PT.DKI) - Idris Nasution, Muhammad; Rifai, Anis (Dinasti Review Publisher, 2024)
Case from PT. Asabri Persero highlighted the important role of BUMN's direction in maintaining company integrity following the principles of Business Judgment Rules (BJR). In the context of BJR, directives have the authority to make business decisions in good faith and rationally, but the case shows alleged violations of integrity and legal compliance by directives, highlighting weaknesses in the company's internal oversight. This research aims to apply the application of the Business Judgment Rule (BJR) in making decisions regarding the direction of BUMN Persero, especially in the context of corruption cases. Normative research methods are used by analyzing legal norms related to BJR and the principles contained therein. The results of the analysis show that the application of the Business Judgment Rule (BJR) in the context of BUMN Persero is important to ensure the sustainability and sustainability of the business. However, in cases of criminal acts of corruption, the application of the Business Judgment Rule (BJR) requires careful adjustments to the principles of transparency, accountability and public interest. In conclusion, the application of the Business Judgment Rule (BJR) in the direction of BUMN Persero's decision-making must be in line with the values ??of integrity and good governance, taking into account the legal consequences that may arise.